PENINGKATAN KETERAMPILAN MEMBACA CEPAT DENGAN MENGGUNAKAN METODE SQ3R DI SEKOLAH DASAR: METODE SQ3R - Lina, Marlina; Aprinawati, Iis; Anggraini, Vitri (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
Learning is an active process when students must directly involved in various learning activities to response stimulus of teachers. The stimulus given by the teacher would be meaningless without their attention and motivation. Growing students motivation can be done by implementation of SQ3R method. SQ3R learning method is a method of learning that implementing to read faster in the childreen. The subject of this research were students of SDN 014 Ganting Damai Grade 5 in academic year2020/2021. Technique of data collection using observation, questionnaire, and achievement test, while the technique of data analysis used descriptive quantitative. Based of the result the average speed read of students in the first cycle is 97 words per minute and the average percentage of understanding the content of reading 70%, the ability of students' reading 68 words per minute. Beside that, In cycle II, the average speed read of the second cycle that is 111 wpm average of understanding the content of reading is 72% and the ability to read quickly 82 wpm. So based on research results SQ3R method can improve students' ability to read quickly. Keywords: Reading Ability, SQ3R Methods. Keywords: Reading Ability, SQ3R Methods